Juicio ético de los contadores: Colegio de Contadores de Pichincha y estudiantes de la Universidad Técnica de Cotopaxi. - García Mera, Luis Antonio (2022)
This research is a contribution to the study of ethics perceived from the accounting branch, taking into account the judgment given both by accountants in the exercise of the profession and those who are in the process of training. Its objective was to identify the differences between the assessment that both groups make in ethics; for which an instrument was applied that allowed assessing the dimensions of public interest commitment, independence, critical judgment, relevance and the ethical challenges faced by the professional. From the data obtained, the analysis of the sociodemographic variables of each group was initially presented, to then estimate the assessment of each of the approaches on a Likert scale (1 being the minimum assessment and 5 the maximum assessment), to obtain valuation by dimension. From these evaluations of the dimensions, the difference in means for each group was estimated, to test the null hypothesis of equality in the evaluations of the students and the professionals in practice, finding that there are significant differences in the dimensions. The analysis was complemented with the identification of the sociodemographic variables that are significant in the explanation of the results, so that it would seem that the experience is the one that conditions the evaluations to a great extent.